Feasibility of high‐dose chemotherapy protocols to treat infants with malignant central nervous system tumors: Experience from a middle‐income country. Issue 1 (24th September 2018) - Elshahoubi, Alya; Khattab, Eman; Halalsheh, Hadeel; Khaleifeh, Kawther; Bouffet, Eric; Amayiri, Nisreen
Abstract: Background: Results of high‐dose chemotherapy (HDCT) protocols for the management of malignant central nervous system (CNS) tumors in infants are mostly reported in high‐income countries. We evaluated the feasibility and results of such protocols in a middle‐income country (Jordan). Methods: A retrospective study of infants' charts with CNS tumors between 2006 and 2015 who were treated according to HeadStart (HS) protocols. Data included patients' demographics, chemotherapy complications, and cost. Results: We identified 18 patients with median age 29 months (range, 9–62 months) at diagnosis (12 HS‐I and six HS‐II). Distribution according to pathology was: atypical teratoid rhabdoid tumors (ATRT) (nine), primitive neuoroectodermal tumors (PNET)/pineoblastoma (five), and medulloblastoma (four). Six patients (33%) had metastatic disease, and 14 (78%) had an incomplete resection. Eleven patients achieved partial or complete remission, two stabilized, and five progressed. Ten patients did not proceed to HDCT due to progression (five), financial reasons (two), failure to collect stem cells (one), and undocumented reasons (two). Seventy‐eight chemotherapy cycles were administered (median interval 26 days). Main complications during induction and consolidation were febrile neutropenia (73% and 100%), documented infections (8% and 13%), and mucositis (12% and 88%), respectively. Three patients developed moderate hearing loss. No protocol‐related mortality was reported. At the last follow‐up, five patients were alive: three with medulloblastoma (19, 29, and 89 months) and two with ATRT (18 and 42 months). Three survivors received focal/craniospinal radiation. The median cost of a complete HS protocol, excluding surgery/radiotherapy, was $103 500 per patient; 39% of the median cost was related to pharmacy expenses. Conclusions: These protocols were manageable in our context of limited health care resources. However, considering the significant costs and the modest survival rate, better selection criteria need to be used to identify patients likely to benefit from this approach.